Enterprise Architecture Planning for College Information Systems using the TOGAF-ADM Framework and ISO 27001 - Hilman, Anwar; Rahayu, Dinar; Susanto, Benny (RISTEC : Research in Information Systems and Technology, 2022)
The planning for the development of Information Systems and Technologyis carried out with themain goal of realizing the Vision and Mission of Higher Education. The Information System design frameworkused is TOGAF (The Open Group Architecture Framework) - ADM (Architecture Development Methode), in that frameworkconsistsof several steps of implementing a representative architectural design to beused in architectural design at the Toyota Indonesia Community Academy which focuseson Business, Data, Applications and Technology. For the information system security management system, TOGAF-ADM can collaboratewith ISO 27001:2013, wherewhen we plan the development of the enterprise information system architecture for universities, we must also focus on information system security in accordance with the information system security system contained in the ISO 27001 :2013. By using a combination framework between TOGAF-ADMand ISO 27001, it is very appropriate to be used as a method for planning Enterprise Architecture in Higher Education that prioritizes business, applicationsand technologyand adopts an information security management system from ISO 27001.